Fortification in view of food items’ mutual influence - Makhynko, Valeriy (My University, 2013)
Considered are the main signs of imbalance of the chemical composition of bakery products. Also pointed to the need to enrich them with consideration of antagonism, and synergies additives. Розглянуто основні ознаки порушення балансу хімічного складу хлібобулочних виробів. Також зазначено на необхідність їх збагачення з урахуванням антагонізму та синергії добавок.
Keywords: chemical composition; enrichment; balance of additives; bakery products; хлібобулочні вироби; баланс добавок; збагачення; хімічний склад; кафедра технології хлібопекарських і кондитерських виробів